Carp Genetic Improvement and Dissemination Program: Progress and Future Pathways - Yeasin, Mohammed; Hamilton, Matthew (WorldFish, 2025)
This presentation was delivered at the workshop “Carp Genetic Improvement and Dissemination: Progress and Future Pathways” held on 24 September 2025 in Khulna, Bangladesh. It highlighted WorldFish’s work on the development and dissemination of improved strains of rohu (Labeo rohita), catla (Catla catla) and silver carp (Hypophthalmichthys molitrix) through family-based selective breeding, currently supported by the CGIAR Sustainable Animal and Aquatic Foods (SAAF) program. The initiative has already released G3 rohu, which has reached more than 200,000 farmers and demonstrated significantly higher growth and profitability. The presentation outlined the planned release of G5 rohu in 2026 and the forthcoming introduction of other improved strains, including G4 silver carp and G3 catla, in the coming years. It underscored the importance of long-term research and dissemination partnerships to sustain and expand these gains. Looking ahead, it emphasized opportunities to refine breeding objectives, apply advanced genomic tools, incorporate new traits and species, use cryopreservation to secure genetic resources, and strengthen quality-assurance systems to safeguard genetic integrity.